BENCHMARKING DALAM ISLAM (IKHTIAR DALAM PENINGKATAN MUTU PENDIDIKAN) - Muhammad Mu'tasim Billah (JUMPA : Jurnal Manajemen Pendidikan, 2020)
One of the terminology that emerged in the world of education is Benchmarking which was born from the business world and began to be applied in the world of education. Benchmarking is used as one of the methods in improving the quality of education by imitating, imitating, measuring or comparing by one organization or institution against other superior or even best organizations or institutions. How in the world of Islamic Education? efforts are needed to dig up information in the teachings of Islam, especially in the main sources of Islamic teachings, namely the Qur'an and Hadith relating to the aim of improving the quality or improvement of the quality of Islamic education. Through a study of the concepts of educational development of the Islamic Khazanah that is available through various literatures, such as Books, Books, journals, to related articles there are no special Terminologies found in common with Benchmarking. However, in the application and steps taken in the Benchmarking concept can be found several Islamic terminology that has a similar value in it. like the concept of Uswah, Muhasabah and Fastabiqul Khairat. Thus, in further research it will be interesting to study more deeply about the application of Uswah, Muhasabah and Fastabiqul Khairat terminology to be applied in improving the quality of Islamic education.Keywords: Benchmarking, Teladan, Islamic Education